Concise Review: Workshop Review: Understanding and Assessing the Risks of Stem Cell-Based Therapies. (26th February 2015) - Heslop, James A.; Hammond, Thomas G.; Santeramo, Ilaria; Tort Piella, Agnès; Hopp, Isabel; Zhou, Jing; Baty, Roua; Graziano, Enrique I.; Proto Marco, Bernabé; Caron, Alexis; Sköld, Patrik; Andrews, Peter W.; et al.
Abstract : Although it is important that stem cell therapies are advanced into the clinic, their safety must be continually evaluated. This review, the result of an Innovative Medicines Initiative SafeSciMET workshop with support from the UK Regenerative Medicine Platform, held at the University of Liverpool, outlines the known risks of stem cell therapeutics and discusses how they can be assessed and managed through preclinical and clinical trials to ensure the safest possible development of new products. Abstract: The field of stem cell therapeutics is moving ever closer to widespread application in the clinic. However, despite the undoubted potential held by these therapies, the balance between risk and benefit remains difficult to predict. As in any new field, a lack of previous application in man and gaps in the underlying science mean that regulators and investigators continue to look for a balance between minimizing potential risk and ensuring therapies are not needlessly kept from patients. Here, we attempt to identify the important safety issues, assessing the current advances in scientific knowledge and how they may translate to clinical therapeutic strategies in the identification and management of these risks. We also investigate the tools and techniques currently available to researchers during preclinical and clinical development of stem cell products, their utility and limitations, and how these tools may be strategically used in the development of these therapies. We conclude that ensuring safety through cutting-edge science and robust assays, coupled with regular and open discussions between regulators and academic/industrial investigators, is likely to prove the most fruitful route to ensuring the safest possible development of new products.